Neural Correlates of Interpersonal Space Permeability and Flexibility in Autism Spectrum Disorder. (29th January 2021) - Massaccesi, Claudia; Groessing, Alexander; Rosenberger, Lisa A; Hartmann, Helena; Candini, Michela; di Pellegrino, Giuseppe; Frassinetti, Francesca; Silani, Giorgia
Abstract: Previous research indicates that the size of interpersonal space at which the other is perceived as intrusive (permeability) and the ability to adapt interpersonal distance based on contextual factors (flexibility) are altered in Autism Spectrum Disorder (ASD). However, the neurophysiological basis of these alterations remains poorly understood. To fill this gap, we used fMRI and assessed interpersonal space preferences of individuals with ASD before and after engaging in cooperative and non-cooperative social interactions. Compared to matched controls, ASDs showed lower comfort in response to an approaching confederate, indicating preference for larger interpersonal space in autism (altered permeability). This preference was accompanied by reduced activity in bilateral dorsal intraparietal sulcus (dIPS) and left fusiform face area (FFA), regions previously shown to be involved in interpersonal space regulation. Furthermore, we observed differences in effective connectivity among dIPS, FFA, and amygdala in ASDs compared to controls, depending on the level of experienced comfort. No differences between groups were observed in interpersonal space regulation after an experienced social interaction (flexibility). Taken together, the present findings suggest that a dysregulation of the activity and connectivity of brain areas involved in interpersonal space processing may contribute to avoidance of physical proximity and social impairments in ASD.